Folk Dances and Their Impact on The Philippine Culture-Based Education - Ramil M. Arciosa; Marlon Nim; Leo Mark Tagupa; Barry Ogod; Lilibeth Dondoyano; Melody L. Cogollo; John Gil Hurtado (Indonesian Journal of Multidiciplinary Research, 2023)
This ethnographic study is founded on the ideas of ethnography and theme analysis, and the information was taken from Department of Education teaching materials, notably those used in the Mother Tongue Basic Language (MTBL) program in the division of Koronadal City. The primary ethnolinguistic group, like the Blaan, has undergone localization, indigenization, and innovation to adapt to changes and develop into a transversal Filipino language as necessary. The significance of the Mla dance of the Blaan Indigenous Community in Sitio Salkan, Brgy. Paraiso is summarized in this study. In terms of their everyday lives, in Brgy. Paraiso, the City of Koronadal is distinctive, especially during the planting seasons for various crops like rice, corn, sweet potatoes, and others. The moon's presence, which the Mla refers to as "Bulen," is the foundation of their dance, as evidenced by their folk literature, "Bulen ne Datu Ulu Eel." This simply indicates that in ancient times, the moon was one of the most important celestial bodies and was regarded as the supreme entity.